(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: COVID-19 is a novel coronavirus which has varies from mild to severe symptoms. This study aimed to determine serum zinc level in COVID-19 patients and find out it's correlation with c-reactive protein. Method: 150 Covid-19 patients, with certain RT-PCR positive result and CT-scan for percentage of lung involvement, were enrolled in the study. Blood samples were collect from the patients for biochemical assessment. Results: The results showed a significant negative correlation between serum zinc with c-reactive protein, percentage of lung involvement and recovery days. Conclusion: zinc is trace element with important body functions and need further studies to enforced its role on COVID-19 inflammatory status.